TECTONICS, GEODYNAMICS AND GOLD MINERALIZATION OF THE EASTERN MARGIN OF THE NORTH ASIA CRATON - Fridovsky V.Y.; Prokopiev A.V. (My University, 2002)
The North Asia craton is a crustal block including the Siberian platform and marginal fold-and-thrust belts. On the eastern margin of the North Asia craton there is the Verkhoyansk fold-and-thrust belt making up the western part of the Verkhoyansk-Chersky collisional orogenic belt extending for 2000 km from the Laptev Sea in the north to the Sea of Okhotsk in the south. A system of frontal thrusts separates the belt from the platform structures. The frontal part of the belt is mainly made of Carboniferous and Permian terrigenous rocks of palaeodeltas and submarine fans which grade eastward into Triassic and Jurassic sediments of the continental slope. The front of the belt is characterized by thrusting and strike-slip faulting with large horizontal displacement. The largest anticlinoria at the front of the belt have a duplex structure. Formation of the major gold deposits and fold and fault structures, as well as igneous activity in the region, are related to the collision of the North Asia craton with the Kolyma-Omolon superterrane and the Okhotsk terrane in the Late Jurassic-Neocomian. The collision occurred in two stages: the early Neocomian frontal collision and the late Neocomian oblique collision.